The Influence of the R2L Learning Model on the Material of the Human Digestive System on Students’ Scientific Literacy - Khairil Arif; Olyivia Retdwina Rusma; Trio Mahendro Alam Sad (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
2018 PISA results show that Indonesia is ranked 71st out of 77 countries in the world. While Indonesia has been successful in increasing the access of 15-year-olds to the school system, greater efforts are still needed to educate them so that the percentage of low-achieving students is kept as low as possible. Based on the results of observations made, students' scientific literacy at SMP Negeri in Bukittinggi is still relatively low. This research was a quasi-experimental study with a non-equivalent control group design which aims to determine the scientific literacy profile of students using the Reading to Learn (R2L) model. The R2L model has a main focus on teaching students to read texts and then gain a deeper understanding of the contents of the reading and rewriting what they have learned (note-taking). Based on the results of statistical analysis, the data is normally distributed and homogeneous so that a parametric test (T-test) is carried out. The results of the calculation of the T-test obtain a value of 0.05, thus H0 is rejected and H1 is accepted. This shows that there is an influence of the Reading to Learn (R2L) model on the digestive system material on the scientific literacy skills of junior high school students.